2022
DOI: 10.1002/slct.202201120
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated Diketopiperazines: Synthesis and Biological Evaluation of Iodinated Analogues of Cyclo(L‐Tyrosine‐L‐Tyrosine) Peptides

Abstract: We developed a simple strategy to diiodinated tyrosine (Tyr) amino acid at the 3‐ and 5‐ positions from the commercially available Fmoc/Boc‐L‐Tyrosine monomer. The iodinated tyrosine monomer have been further adopted to generate a variety of iodinated Fmoc tyrosine dimers. Upon Fmoc elimination, we obtained diketopiperazine (DKP) analogues of Cyclo(L‐Tyr‐L‐Tyr) with varied number of iodine atoms. We also report the biological studies of these iodinated DKP analogues in three different cancer cell lines. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previously, halogenation strategy has been successfully used to confer and alter supramolecular behavior for peptides, 24 which, for example, was found to promote the self‐assembly of amyloidogenic peptides 25–28 and diphenylalanine peptides 29 through well‐organized halogen bonds. In addition, the halogen bonds have also been exploited as a powerful tool to modulate peptide conformation 30 and to improve the cytotoxic activity of peptides agents against cancer cells 31 . In this study, we demonstrated that although AF17121 can bind to IL‐5R in a good potency, the peptide exhibits a wide specificity and promiscuity toward the IL‐R family due to the high conservation of the family members in sequence, structure and function.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previously, halogenation strategy has been successfully used to confer and alter supramolecular behavior for peptides, 24 which, for example, was found to promote the self‐assembly of amyloidogenic peptides 25–28 and diphenylalanine peptides 29 through well‐organized halogen bonds. In addition, the halogen bonds have also been exploited as a powerful tool to modulate peptide conformation 30 and to improve the cytotoxic activity of peptides agents against cancer cells 31 . In this study, we demonstrated that although AF17121 can bind to IL‐5R in a good potency, the peptide exhibits a wide specificity and promiscuity toward the IL‐R family due to the high conservation of the family members in sequence, structure and function.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, the halogen bonds have also been exploited as a powerful tool to modulate peptide conformation 30 and to improve the cytotoxic activity of peptides agents against cancer cells. 31 In this study, we demonstrated that although AF17121 can bind to IL-5R in a good potency, the peptide exhibits a wide specificity and promiscuity toward the IL-R family due to the high conservation of the family members in sequence, structure and function. We further improved the binding affinity of AF17121 to IL-5R and the recognition selectivity of AF17121 for IL-5R over other IL-Rs by gluing rationally designed halogen bonds at the protein-peptide complex interface.…”
mentioning
confidence: 78%